2011
DOI: 10.1038/jid.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Shows Altered Expression of Wnt Pathway– and Lipid Metabolism–Related Genes as Well as Melanogenesis-Related Genes in Melasma

Abstract: Melasma is a commonly acquired hyperpigmentary disorder of the face, but its pathogenesis is poorly understood and its treatment remains challenging. We conducted a comparative histological study on lesional and perilesional normal skin to clarify the histological nature of melasma. Significantly, higher amounts of melanin and of melanogenesis-associated proteins were observed in the epidermis of lesional skin, and the mRNA level of tyrosinase-related protein 1 was higher in lesional skin, indicating regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 27 publications
7
113
2
4
Order By: Relevance
“…Bioinformatics studies have shown that genes responsible for melasma include Wnt and lipid metabolism-related genes in addition to melanogenic markers (Kang et al 2011) and that reduced expression levels of WIF-1 (Wnt inhibitory factor-1) in keratinocytes and/or fibroblasts may play roles in the development of melasma (Kim et al 2013). Patients with mastocytosis usually carry the D816 V KIT mutation and a bioinformatics study shows that those patients show the up-regulation of genes involved in innate and inflammatory immune responses, including interferon-induced genes and genes involved in cellular responses to viral antigens, together with complement inhibitory molecules and genes involved in lipid metabolism and protein processing.…”
Section: Acquired Hyperpigmentation Disordersmentioning
confidence: 99%
“…Bioinformatics studies have shown that genes responsible for melasma include Wnt and lipid metabolism-related genes in addition to melanogenic markers (Kang et al 2011) and that reduced expression levels of WIF-1 (Wnt inhibitory factor-1) in keratinocytes and/or fibroblasts may play roles in the development of melasma (Kim et al 2013). Patients with mastocytosis usually carry the D816 V KIT mutation and a bioinformatics study shows that those patients show the up-regulation of genes involved in innate and inflammatory immune responses, including interferon-induced genes and genes involved in cellular responses to viral antigens, together with complement inhibitory molecules and genes involved in lipid metabolism and protein processing.…”
Section: Acquired Hyperpigmentation Disordersmentioning
confidence: 99%
“…Yet there is a paucity of data about the difference in the degree of mRNA transcription of the above genes between melasma lesional skin and normal adjacent one. There was only one previous transcriptomic study in this series: Kang et al [9] reported that there was up-regulation of genes involved in the melanogenesis and Wnt signaling and down-regulation of those involved in the lipid metabolism in melasma lesional skin compared with normal adjacent one. In addition, it has also been reported that H19 gene and Wnt inhibitory factor-1 (WIF-1) are down-regulated and PDZ domain protein kidney 1 (PDZK1) is up-regulated in melasma lesional skin [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] More recently, the molecular signaling mechanisms responsible for upregulating and downregulating the genetic pathways leading to hypermelanogenesis have been identified including the Wnt pathway, c-kit and the role of dermal stem cells, although what actually triggers the respective signaling process remains to be elucidated. 5,6) A large variety of topical therapeutic approaches has been reported including bleaching agents (hydroquinone and kojic acids) and chemical peels (retinol, trichloroacetic or kojic acid), but although some success has been reported with these, the results are somewhat inconsistent with undesirable side effects such as unwanted pigmentary changes and dermatitis, 7) and their efficacy appears to decrease with long-term use. In the past few years, intense pulsed light (IPL) systems have been reported in the treatment of mild melasma in the Japanese skin, 8) and pigment-selective visible light lasers, but the results were less than expected with side effects related to excess photothermal damage to the epidermis and dermis associated with these systems, particularly post-inflammatory secondary hyperpigmentation (PIH).…”
Section: Original Articlesmentioning
confidence: 90%